Vital Problems of the Career Guidance Work in Higher Education Establishments: The Socio-Economic Context - Cherusheva, H. B.; Syniakov, А. V. (Statistics of Ukraine, 2020)
The latest years are marked by the considerably aggravated demographic situation in Ukraine, which enhanced the competition among higher education establishments (HEEs) on the education services market and intensified the vocational guidance work in HEEs among student youth. The vocational guidance work, gaining special significance as early as in times of Ukraine’s transition to the market economy, still remains an important element of the government policy. It helps identify and purposefully develop talents and inclinations of a person, his/her professional and cognitive interests regarding the choice of future specialty, effectively increase his/her social and professional mobility and form his/her needs and willingness to labor activities. The authors justify the need for essential change in the higher education system of Ukraine. The social background for the professional choice, the dynamics of value orientations and values of student youth, specifics of the vocational guidance work in HEEs are studied by case of the National Academy of Statistics, Accounting and Audit (NASAA). Details of the system for vocational guidance work in NASAA are given, with formulating its core objectives and outlining the phases and areas of implementation. Results of a survey lead the authors to the conclusion about a gap between the needs of the labor market in highly skilled specialists, on the one hand, and the professional orientations and choices of student youth, on the other, resulting in a higher probability of casual entrances of applicants to HEEs. This gives birth to moral and psychological collisions of the personal nature, with the subsequent dissatisfaction with the chosen profession, staff turnover and migration of young specialists across economic sectors. It is revealed that full-fledged and comprehensive information and education efforts and qualified vocational guidance services on professional choice rendered to student youth can be most effective given the concerted actions of HEEs, schools and other social institutes. The authors’ studies allow them to identify problematic points in the vocational guidance work and outline the main areas of further improvements in the vocational guidance.